Pre-harvest conditions affecting the export quality of muskmelons (Cucumis melo L.) - Combrink, Nicolaas Johannes Jacobus (Stellenbosch : Stellenbosch University, 2012)
Dissertations (Ph. D. Agric.) -- University of Stellenbosch, 1995.